2022
DOI: 10.3390/su14063212
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Survival Ability of Franchise Industries during the COVID-19 Crisis in Malaysia

Abstract: Since the world was hit by the COVID-19 pandemic crisis that began in December 2019, many industries have been affected, including the franchise industry in Malaysia. Thus, the COVID-19 pandemic has had a great impact on business survival. Direct effects can be seen in reduced income, job losses, changes in customer preferences, and business relationships between franchisors and franchisees. Some franchises have had to close their operations, and others still struggled to survive during the pandemic crisis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…With the government's support, the franchise industry is expected to be boosted mainly by homegrown franchisors. A study finding by Aziz et al [38] clearly showed that the government and franchise-related organisations encourage franchising owners to continue and sustain their firms with financial assistance, virtual franchise exhibition, business development grants and training and support. To achieve that goal, the government has launched several programmes to provide the necessary environment, resources, and incentives to expedite the growth of franchise entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the government's support, the franchise industry is expected to be boosted mainly by homegrown franchisors. A study finding by Aziz et al [38] clearly showed that the government and franchise-related organisations encourage franchising owners to continue and sustain their firms with financial assistance, virtual franchise exhibition, business development grants and training and support. To achieve that goal, the government has launched several programmes to provide the necessary environment, resources, and incentives to expedite the growth of franchise entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Aziz et al [38] proposed that continuous government financial assistance is favourably associated with the Malaysian franchising business society's capacity to survive the pandemic. This is because constant processes are critical for recognising the relevance of sustainable growth to the business environment [93].…”
Section: Government Supportmentioning
confidence: 99%
“…The direct effects of the coronacrisis were observed in most countries (Balasoiu 2021;Abd Aziz et al 2022;Turnea et al 2020) in terms of reduced income, job losses, customer preferences, low demand, cash flow problems, obstacles to the free flow of capital, labour and trade. Companies in some sectors have lost up to 60% of their intrinsic value in one year (Rizvi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have examined the growth and success of franchises within mature markets by analyzing factors such as operational systems, relationship dynamics between franchisors and franchisees, and the impact of franchising on economic development. As globalization progressed and multinational corporations sought new avenues for growth, attention shifted towards investigating the expansion of franchising into emerging markets such as Asia, South America, and Africa (Abd Aziz et al, 2022;Choo, 2005;Combs et al, 2004;Flores Villanueva et al, 2023;Michael, 2014;Zamberi Ahmad, 2012). Studies have begun to explore the challenges and opportunities presented by these markets, including cultural differences, legal and regulatory frameworks, consumer behavior, and market conditions.…”
Section: Introductionmentioning
confidence: 99%